Variability of on-treatment platelet reactivity in patients on clopidogrel. (August 2014) - Freynhofer, Matthias K.; Bruno, Veronika; Brozovic, Ivan; Jarai, Rudolf; Vogel, Birgit; Farhan, Serdar; Hübl, Wolfgang; Willheim, Martin; Wojta, Johann; Huber, Kurt
Abstract Response to clopidogrel therapy is subject to inter-individual variability. However, data with regard to on-treatment platelet reactivity over time in patients undergoing coronary stenting are scarce. For this prospective observational study, 102 consecutive patients on dual antiplatelet therapy undergoing coronary stenting due to stable coronary artery disease (CAD; n = 29), non ST-elevation acute coronary syndrome (NSTE-ACS; n = 45) and ST-elevation myocardial infarction (STEMI; n = 28) were enrolled. Vasodilator-stimulated phosphoprotein-phosphorylation assay was performed at baseline, as well as 1, 3 and 6 months thereafter. Platelet reactivity index (PRI) measured after 1, 3 and 6 months was lower compared to baseline values (p < 0.001). Variables responsible for reduced response to clopidogrel at baseline (reticulated platelet fraction, simvastatin therapy) and during steady-state phase (body mass index, blood glucose concentrations, cholesterol/HDL-ratio and quality of life score) were different. High on-treatment platelet reactivity (HTPR)-phenotype (cut-off = 50% PRI) within the first month changed in 31% of stable CAD, 33% of NSTE-ACS and 39% of STEMI patients, respectively. HTPR-phenotype in the steady-state phase (month 1 to 6) changed in 45% of stable CAD, 33% of NSTE-ACS and 25% of STEMI patients. Response to clopidogrel and accordingly platelet function might vary over time, especially when a cut-off based approach, is used. There was a significant reduction of on-treatment platelet reactivity within the first month after percutaneous coronary intervention with stenting which was maintained for up to 6 months. Variables associated with reduced response to clopidogrel at baseline and during steady-state phase were different, as the latter mainly reflected an unfavorable metabolic profile, comprising elevated BMI, blood glucose levels as well as cholesterol/HDL-ratio.